2009
DOI: 10.1111/j.1440-1746.2009.05797.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil, a phosphodiesterase‐5 inhibitor, on acetic acid‐induced colonic inflammation in the rat

Abstract: Sildenafil citrate administration to rats with acetic acid-induced colitis seems to be beneficial via prevention of lipid peroxidation, oxidant generation, cytokine production and neutrophil accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 26 publications
3
32
1
4
Order By: Relevance
“…Toxic oxidants can cause damage if the capacity of the endogenous antioxidant enzymes as SOD, catalase and glutathione peroxidase cannot cope with their excess production. Thus, increased oxidative stress and impairment of the antioxidant defenses by the deleterious effect of ROMs contributes to the pathogenesis of colitis (Iseri et al, 2009). It was previously found that oxidative stress and its consequent lipid peroxidation results in increased colonic MDA contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic oxidants can cause damage if the capacity of the endogenous antioxidant enzymes as SOD, catalase and glutathione peroxidase cannot cope with their excess production. Thus, increased oxidative stress and impairment of the antioxidant defenses by the deleterious effect of ROMs contributes to the pathogenesis of colitis (Iseri et al, 2009). It was previously found that oxidative stress and its consequent lipid peroxidation results in increased colonic MDA contents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sildenafil, a prototype of PDE5I has shown good effects in experimental colitis by balancing oxidant-antioxidant status and inhibiting ROM production and release of cytokines (Salari-Sharif and Abdollahi, 2010). In a rat model of colitis, Sildenafil prevented lipid peroxidation, cytokine production and neutrophil accumulation, Sildenafil reversed TNF-α and IL-1β in the colitis back to the control value (Iseri et al 2009). A recent study confirmed the anti-inflammatory effect of a PDE5I in a colitis model in rats (Margonis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[20] Moreover, the beneficial effects of sildenafil have been shown in the balance of oxidation and antioxidation via decreasing oxidative and nitrosative stress in inflammatory events. [9,23,[30][31][32][33][34] However, there is no study in the literature focusing on the effects of sildenafil in remote organ injury induced by severe burn except our previous study focusing on acute lung injury. [9] The purpose of the present study was to evaluate the effects of different dosages of sildenafil in distant organs, such as liver and kidneys, due to severe scald burn injury in rats.…”
Section: Introductionmentioning
confidence: 98%
“…in ischemic colonic anastomoses increased GSH levels and promoted healing of anastomosis. Additionally, Iseri et al [33] found that sildenafil treatment (5 mg/kg/p.o.) decreased MDA and increased GSH levels in tissues and improved the healing of colonic inflammation in rats.…”
mentioning
confidence: 99%
“…Recently, several studies have shown that, in addition to treating erectile dysfunction, sildenafil can prevent or decrease tissue injury. Two previous studies demonstrated the beneficial anti-inflammatory effect of SIL on acetic acidinduced acute colitis and bleomycin-induced lung fibrosis models in rats via prevention of lipid peroxidation, oxidant generation, cytokine production and neutrophil accumulation (Iseri et al, 2009;Yildirim al., 2010).…”
Section: Introductionmentioning
confidence: 99%